2022
DOI: 10.1097/prs.0000000000009773
|View full text |Cite
|
Sign up to set email alerts
|

Sensory restoration in abdominally-based free flap for breast reconstruction using nerve allograft

Abstract: Background: Neurotization in breast reconstruction can be performed with the aid of nerve grafts and conduits to decrease the tedious dissection and overcome size mismatch. However, there has yet to be a formal analysis of this approach. The goal of this study was to evaluate sensory recovery after neurotized abdominally based free flaps for breast reconstruction using the authors’ novel technique and analyze factors that could affect sensory recovery. Methods: A novel technique using processed nerve allogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Although numerous publications have reported improved outcomes with breast neurotization, results can vary due to differences in techniques. [1][2][3][4][5][6][7][8][9][10][11][12]18,19 The combination of nerve-sparing mastectomy and breast neurotization with autografts or allografts may enhance sensory recovery in the breast. For reliable evaluation of outcomes, standardization of nervesparing mastectomy and NAC neurotization techniques is essential.…”
Section: Next Stepsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although numerous publications have reported improved outcomes with breast neurotization, results can vary due to differences in techniques. [1][2][3][4][5][6][7][8][9][10][11][12]18,19 The combination of nerve-sparing mastectomy and breast neurotization with autografts or allografts may enhance sensory recovery in the breast. For reliable evaluation of outcomes, standardization of nervesparing mastectomy and NAC neurotization techniques is essential.…”
Section: Next Stepsmentioning
confidence: 99%
“…The restoration of sensation after mastectomy has been reported, albeit with varying rates of success. 4–13 The absence of sensory perception in the chest wall or reconstructed breast not only impacts a patient’s psychological well-being but also presents the risk of potential thermal injuries due to the lack of protective sensation. 14–16…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,9,20 A likely component of the improved sensation in the autologous cohort was the neurotization of the abdominal flap to the third intercostal nerve using a nerve allograft. Djohan et al 22 demonstrated that breasts reconstructed with abdominal flaps which have been neurotized in a similar fashion develop increased sensation compared with nonneurotized controls.…”
Section: Discussionmentioning
confidence: 99%
“…Emphasis on standardization of technique and outcomes measurements has been seen in recent years to help optimize outcomes, including the creation of a multi-site prospectively collected registry that has been shown to have promising early results ( 33 ). Most recently, Djohan et al reported outcomes from a large case-control study looking at neurotization with nerve allografts in combination with nerve conduits during abdominally based free flap reconstruction, with significantly improved sensation seen at 1-year follow-up in the neurotized cohort ( 34 ). Another large study assessing delayed-immediate reconstruction with neurotized DIEP flaps showed return to baseline sensation in nearly all quadrants of the breast at 2-year follow-up ( 35 ).…”
Section: Immediate Sensory Nerve Reconstruction: Technique and Outcomesmentioning
confidence: 99%